Mima game corner / Mohd Izwan Awang Sulong and Mohammad Asyraf Mastapa - Awang Sulong, Mohd Izwan; Mastapa, Mohammad Asyraf (2017)
MIMA Game Corner expects to launch in June 2018 and will offer game playing facilities initially in Shah Alam, Selangor. The service offered will be for game players to have a unique experience of playing video games on world class facilities. The target group of customers is children, youths, adults and anyone who is interested in leisure and video games. MIMA Game Corner plans for a strong market entrance by offering up to date versions of games of PlayStation 4 (PS4). The company will entertain users with the best video gaming experience possible and a facility which is impossible to be recreated at home. The facility shall have other games such as arcade games, shooting games, strategy games, sport games, adventurous games, etc., with single and multiplayer options.